Peran Kepemimpinan Pendidikan dalam Meningkatkan Efektifitas Manajemen Kearsipan di Era Digital - Azizah, Ema Ainun; Hasanah, Kamilia Qotrunnada; Munandar, Rafael Aditya Ali; Pratiwi, Silvi Itsna Ginting; Siswadi (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the crucial role of educational leadership through transformational, visionary, and spiritual approaches in enhancing the effectiveness of archive management in the digital era. The method used is a literature study with descriptive analysis of educational management literature and current archival regulations. Data collection techniques are carried out through documentation processes and systematic literature searches using academic databases such as Google Scholar, Garuda, and national and international journal databases. The data analysis technique in this study uses qualitative descriptive analysis with a thematic approach, involving stages of data reduction, data presentation, and drawing conclusions. The findings indicate that adaptive and integrity-driven leadership is the main determinant of successful digital transformation. Leaders who act as visionary navigators are able to integrate Information and Communication Technology (ICT) with the institution's ethical values while also building a digitally literate organizational culture. The synergy between providing reliable infrastructure, continuously developing staff competencies, and managerial supervision based on SOPs has been proven to create efficient, secure, and accountable records management to support data-driven decision making